A Study on Novel - a Tale of Two Cities: Exploring the Unconventional Side of Charles Dickens (Journal of Advances and Scholarly Researches in Allied Education, 2014)
A Tale of TwoCities is perhaps the least characteristic ofCharles Dickens's works. Unlike both his earlier and his later novels, whichare largely concerned with events within the Victorian society in which helived, A Tale of Two Cities isset during a period some seventy years earlier. It shows both France andEngland in an unflattering light. Perhaps because the novel is souncharacteristic of the author, it remains among the author's most popular workswith readers who do not generally enjoy Dickens. On the other hand, it is oftenrated the least popular Dickens novel among Dickens fans.